Bacteriology Ozena - Monteverde, Juan A. (1918)
For some time I have focused my research laboratory to study the bacteriology of this troublesome disease, or of this foetid ozeria hypertrophic rhinitis, which is the source for all this trouble hapless patients and makes them unwelcome company. Not the case make a detailed list of the already rich literature of ozena or enter considerations of etiology and pathogenesis of the disease, which have been duly considered, just limit myself to summarily expose some facts necessary to present the result of my research.